PEMBATALAN SERTIFIKAT HAK MILIK NOMOR 289 DESA KEDARPAN KECAMATAN KEJOBONG KABUPATEN PURBALINGGA (Studi Putusan Mahkamah Agung Republik Indonesia Nomor 1085K/PDT/2006 Tanggal 25 April 2007) - Runtut Puji Setiyadi (MIH Unsoed, 2015)
Certificate is evidence of a strong right, meaning that should be considered true until proven otherwise in court with other evidence. Certificate of ownership of land rights can be canceled if the decision is flawed law in publishing or implement court decisions that have binding. This study aims to examine: First, legal considerations in the decision of the Supreme Court judges case of cancellation of land titles certificate No. 289 Rural District of Kejobong Kedarpan Purbalingga In the Supreme Court Decision No. 1085K/PDT/2006 April 25, 2007. Second, theoretical overview sense of justice contained in the Supreme Court decision No. 1085K/PDT/2006 Date 25 April 2007. This study uses normative juridical approach. Data were analyzed using qualitative normative method. Based on the results of research and discussion can be concluded as follows: First, the law judge of the Supreme Court judgment in the case of cancellation verdict land ownership certificate No. 289/Rural District of Kejobong Kedarpan Purbalingga the Supreme Court Decision No. 1085K/PDT/2006 On 25 April 2007, because of legal disability certificate obtained from a tort. Second, the Supreme Court decision No. 1085K/PDT/2006 April 25, 2007 already provides a sense of justice, namely maintaining the rights of the individual and gives the right to every person entitled to receive it.Keyword : Land Certificate, Privillage